2019
DOI: 10.1182/blood-2019-121899
|View full text |Cite
|
Sign up to set email alerts
|

Net Clinical Benefit of Low Dose Rivaroxaban in Coronary Heart Disease: A Systematic Review and Meta-Analysis

Abstract: Introduction US Food and Drug Administration has recently approved the use of rivaroxaban 2.5mg BID in patients with coronary heart disease based on Cardiovascular Outcomes for People Using Anticoagulation Strategies (COMPASS) trial. However, it's unclear whether there is net clinical benefit with use of rivaroxaban in such patients. Therefore, we did a systematic review and meta-analysis to evaluate the effects of rivaroxaban on clinical outcomes in coronary heart disease patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Nonetheless, recently meta‐analyses demonstrated the addition of rivaroxaban to APT regimen was effective in patients with CAD, but the safety outcome was doubtful 10‐12 . Interestingly, Chiarito et al 13 found the risk–benefit profile of DOAC appears unfavorable in patients with NSTE‐ACS, whereas DOAC in addition to APT might represent an attractive option for patients with STEMI.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, recently meta‐analyses demonstrated the addition of rivaroxaban to APT regimen was effective in patients with CAD, but the safety outcome was doubtful 10‐12 . Interestingly, Chiarito et al 13 found the risk–benefit profile of DOAC appears unfavorable in patients with NSTE‐ACS, whereas DOAC in addition to APT might represent an attractive option for patients with STEMI.…”
Section: Introductionmentioning
confidence: 99%